Post traumatic growth (PTG) in university students after the COVID-19 pandemic - Sreekumar, Archana (Nanyang Technological University, 2024)
A recent traumatic event that has influenced the lives of many is the COVID-19 Pandemic. A traumatic event shatters an individual's worldviews and perceptions. However, individuals can derive positive meaning out of such an event, and this phenomenon can be termed as Post-Traumatic Growth (PTG). However, there has been no research done on the development of PTG in university students in the face of the pandemic. The present study aims to close this gap by investigating the development of PTG in university students. The present study conducted qualitative analysis on findings from a larger cross-sectional mixed methods study on understanding and strengthening university students’ psycho-socio- emotional wellness and preparedness for future pandemic. Participants aged between 18 and 30 years old were recruited from Nanyang Technological University (NTU) to participate in the quantitative interview. A nested sample of 48 undergraduate students was invited to participate in the qualitative interviews. In the present study, the interviews of 10 students were transcribed using intelligent verbatim. In the results, 4 dimensions of PTG, enhanced relationships, personal empowerment, enlightened existence and finding new possibilities. 4 factors (active coping, perceived social support, mindful positivity, and technology) were identified to support PTG while 2 factors (maladaptive coping and lack of perceived social support) were identified to hinder PTG. As found in other literature, these factors were identified to the development of resilience as well. Hence, moving forward, universities can target developing factors that aid the development of resilience to empower students to overcome future traumatic and environmental stressors.